Influence of Use Gadgets Towards Political Cultural Orientation - Fernanda, Fitra Endi; Pratama, Rendy Yudha; Habibi, Roy Kembar (UNIVERSITAS PGRI YOGYAKARTA, 2022)
AbstractThis study aims to determine the effect of the utilization of gadgets as political communication on the political culture orientation of students in senior high school. The design in this study is descriptive research using a quantitative approach and using correlational research. The sample in this study was taken from the population with a proportional purposive sampling technique that was as many as 347 students. The results of this study indicate that there is a positive and significant influence on the utilization of gadgets for political communication. This is indicated by the t-count values is 6,398> t-table (6,398 > 1,649) and a significance value <0.05 (0.000 < 0.05).Keywords: Gadgets, Media, Political Communication, Political Culture, Student